Enlightening on Effectual Ayurvedic Therapeutics in Early Diagnosed Type 2 Diabetes Mellitus (International Journal of Ayurveda and Pharma Research, 2025)
Diabetes mellitus is a lifestyle-related disease that has been recognized and described in Ayurvedic literature since ancient times. It is termed as Prameha vyadhi in Ayurveda. The characteristic symptom of the DM (Prameha) is polyurea (Bahu mutrata). It mainly causes due to Kaphaprakopak aahar-vihar. Due to this metabolic dysfunction occurs and it hampers the healthy life of a person. It affects both mental and physical health. This case study is about the male patient of age 38 years old. He came with early diagnosed type 2 diabetes to Jeena Sikho Lifecare Limited Clinic, Sangrur, Punjab on 30/11/2023. He had complaints like burning sensation in eyes, tingling numbness in legs etc. On the basis of Ayurvedic criteria he was diagnosed as Pittanubandhi Kaphaj Prameha. Ayurvedic treatment not only includes medications but also includes do’s and don’ts for diet and lifestyle (Pathya-apathya). Various drugs like Haridra, Amalaki, Shilajeet etc. are used in the above-mentioned case. This study enlightens that how ayurvedic treatment can reverse the diabetes if it is diagnosed early. Investigation reports reveal a catching reduction in HbA1c and mean blood glucose level after treatment. This ongoing case study enlightens the effectual Ayurvedic therapeutics for diabetes.